Transforming agricultural water management through the water–energy–food nexus: trends, opportunities, barriers and solutions - Nhamo, L.; Taguta, C.; Mpandeli, S.; Dirwai, Tinashe Lindel; Liphadzi, S.; Mabhaudhi, T. (Wiley, 2025)
Agricultural water management (AWM) is increasingly transitioning towards transformative thinking, where interconnected sectors, including water, energy and food, are managed holistically. Trends point towards cross-sectoral and harmonised strategies to optimise water use efficiency and productivity, integrate renewable energy, promote sustainable food production and strengthen ecological resilience while considering economic incentives for farmers. However, the main challenge of AWM has been managing water and energy for food production amidst the scarcity, degradation and depletion of water resources. This requires a shift from the current AWM practices, which focus on single-factor productivity and resource use efficiency at the expense of equity, conservation, consumption and the circular economy. This entails reducing water consumption, increasing environmental flows, minimising waste and reusing resources in agriculture. This systematic review identifies pathways to transition traditional AWM practices to a water–energy–food (WEF) nexus-informed system that is equitable, inclusive, integrated and resilient, balancing the socio-ecological systems. This review establishes the interlinkages of WEF resources as drivers of resource use efficiency in sustainable crop production, highlighting the trends, opportunities, barriers and solutions of a smart AWM system. The recommendations propose shifting from the current production-centric AWM to one that is transformative, equitable, sustainable and resilient for human and natural systems.